Household Over-indebtedness: Understanding its Extent and Characteristics of those Affected. (1st July 2016) - Ntsalaze, Lungile; Ikhide, Sylvanus
Abstract: Household over-indebtedness has become a matter of concern across the world, in so far, as its social implications are concerned. The objective of this paper is to provide a snapshot of the prevalence of overindebtedness, using various indicators, and describe which households are over-indebted. In terms of the National Credit Regulator indicator, 8 percent of South African households are over-indebted. Results also show that, under the unsecured debt indicator, 15.2 percent of households are over-indebted, and 11 percent of households are driven below the relative income poverty line after making debt repayments. Most over-indebted households are found in the lowest income category, do not receive government grants and have an unemployed household head.